Reduced architecture for simultaneous correlation of orthogonal sets of complementary sequences - Funes, Marcos Alan (2010)
An architecture that enables to perform the simultaneous correlation of four sets of complementary sequences is presented. The proposal is based on the properties of orthogonal sets as well as on the use of a recursive generation algorithm. Theoretically demonstrated, it constitutes a remarkable advance in the practical application of complementary sequences in platforms with limited resources.